RELEGIUSITAS BANTEN SIAP SAJI DI TENGAH TRANSFORMASI BUDAYA MASYARAKAT BALI - I Wayan Suharta (UHN IGB Sugriwa Denpasar, 2022)
In Bali, most of the cycles of religious life are controlled by ceremonial activities of a religious nature. Ceremonial activities are not only a necessity but also a necessity. It makes sense if later the Hindus in Bali became ceremonial people, they worshiped themselves, others, including nature and the environment. As a result of their very limited abilities, Hindus use facilities in the form of banten as a form of offering. Religious activities that use offerings are quite dense. The choice of